Effectiveness of Anti-Bullying Program in Enhancing Positive School Climate in Middle Schools - Imha, Ulia Arbarehan; Al-Momani, Ammar; Hamdan, Salma (World Psychology, 2025)
Bullying in schools is a pervasive issue that negatively impacts students’ mental health, academic performance, and overall school climate. A positive school climate is essential for fostering an environment conducive to learning, where students feel safe, respected, and supported. Anti-bullying programs have been implemented to address this problem; however, their effectiveness in enhancing school climate, particularly in middle schools, remains underexplored. This study aims to evaluate the effectiveness of an anti-bullying program in improving the school climate in middle schools. The research utilizes a quasi-experimental design, with 300 students from three middle schools participating in the study. Pre- and post-program surveys were administered to assess students’ perceptions of school climate, including safety, respect, and inclusiveness. The results indicate a significant improvement in the overall school climate, with increased perceptions of safety and respect, and a reduction in bullying behaviors. Students reported feeling more supported and engaged in the school community after the program. The study concludes that anti-bullying programs can be highly effective in fostering a positive school climate, providing a safer and more supportive environment for students. The findings suggest that implementing such programs in middle schools can significantly contribute to improving the educational experience and well-being of students.